Biculturalism and Inclusion in New Zealand: The Case of Orakei - Kawharu, I.H. (Anthropologica, 2022)
The author applies Schwimmer's dual concepts "biculturalism and inclusion" to the relationship between an indigenous tribal community, Ngati Whatua and the city, Auckland, in which it is located. The study is an account of developments made possible by the return of land to the community following a tribunal enquiry.